A biotroph sets the stage for a necrotroph to play: ‘Candidatus Phytoplasma solani’ infection of sugar beet facilitated Macrophomina phaseolina root rot - Duduk, Nataša; Vico, Ivana; Kosovac, Andrea; Stepanović, Jelena; Ćurčić, Živko; Vučković, Nina; Rekanović, Emil; Duduk, Bojan (Frontiers in Microbiology, 2023)
‘Candidatus Phytoplasma solani’ (stolbur phytoplasma) is associated with rubbery taproot disease (RTD) of sugar beet (Beta vulgaris L.), while Macrophomina phaseolina is considered the most important root rot pathogen of this plant in Serbia. The high prevalence of M. phaseolina root rot reported on sugar beet in Serbia, unmatched elsewhere in the world, coupled with the notorious tendency of RTD-affected sugar beet to rot, has prompted research into the relationship between the two diseases. This study investigates the correlation between the occurrence of sugar beet RTD and the presence of root rot fungal pathogens in a semi-field ‘Ca. P. solani’ transmission experiment with the cixiid vector Reptalus quinquecostatus (Dufour), in addition to naturally infected sugar beet in the open field. Our results showed that: (i) Reptalus quinquecostatus transmitted ‘Ca. P. solani’ to sugar beet which induced typical RTD root symptoms; (ii) Macrophomina phaseolina root rot was exclusively present in ‘Ca. P. solani’-infected sugar beet in both the semi-field experiment and naturally infected sugar beet; and that (iii) even under environmental conditions favorable to the pathogen, M. phaseolina did not infect sugar beet, unless the plants had been previously infected with phytoplasma.